The Effect of Direct Instruction Learning Model on The Forearm Pass Learning Outcome in Volleyball - Setiawan, Anang; Kharisma, Yudhi; Yohan, Sandi (Universitas Pendidikan Indonesia, 2020)
Direct Instruction learning model is a model that is widely used in physical education learning. However, some steps in the implementation of this this model are sometimes ignored which affects the learning outcomes. The purpose of this study was to determine the effect of Direct Instruction learning models on learning outcomes of the volleyball underpass. This research was an experimental research using One-Group Pre-test-Post-test Design. The subjects of the study were 32 students, consisting of 15 male students and 17 female students aged 13 years in average. Volleyball skill test instruments were used in this study. The results of the study show a significant increase of the average scores. The study implies that the Direct Instruction learning model would affect learning outcomes of volleyball underpass if all steps of this model are implemented